Gen Z’s Perception of Using Instagram Content as a Media for Learning English Vocabulary - Putri Dyanita Nur Faatihah; Eulis Rahmawati (Universitas Uluwiyah Mojokerto, Indonesia., 2026)
This study investigates Generation Z's perception of using Instagram content as a medium for English vocabulary learning, focusing on the @kampunginggrislc account. Gen Z's often low interest in mastering vocabulary is frequently attributed to monotonous and unengaging learning methods. Therefore, the integration of social media, particularly Instagram, which is highly popular among Gen Z, becomes a relevant alternative. This research aims to understand Gen Z's perception of the effectiveness of Instagram content in vocabulary learning, as well as how content design influences their learning interest. This research employed a descriptive qualitative method, involving 20 Gen Z respondents aged 17–25 years who are followers of the @kampunginggrislc account. Data were collected through open-ended questionnaires distributed online. The findings indicate that the majority of respondents have a positive perception of the Instagram content. Based on Stephen P. Robbins theory of perception encompassing the stages of acceptance, understanding, and evaluation respondents accepted the content well, understood the material easily and enjoyably, and evaluated the content as effective in enhancing vocabulary mastery. Furthermore, content design also proved to significantly influence Gen Z's learning interest. Appealing visual design, interactive features like quizzes and games, and the use of slang and everyday expressions are highly compatible with Gen Z's learning styles and digital habits. This makes the learning process more enjoyable, flexible, and relevant to their lives. Thus, the use of Instagram content, particularly from the @kampunginggrislc account, can be an effective alternative English vocabulary learning medium for Generation Z.